Anti-inflammatory and immunomodulatory potential of lignans from Artemisia cina: Integrated quantum, docking, and cytokine expression studies - Montserrath Abigail León Flores; Jocelyn Maza López; Sergio David Zavaleta Iglesias; Jorge Alfredo Cuéllar-Ordaz; Héctor Alejandro de la Cruz-Cruz; Maria Inés Nicolás Vázquez; Joel Martinez; Gerardo Ramírez Rico; Cynthia González-Ruiz; María Eugenia López-Arellano; Rosa Isabel Higuera-Piedrahita (PLoS ONE, 2026)
Quantum, docking, and in vitro studies were performed to evaluate the immunomodulatory function of two lignans isolated from Artemisia cina —3-demethoxy-6-O-demethylisoguaiacin ( L1 ) and norisoguaiacin ( L2 )—through individual molecular docking with cyclooxygenase-2 (COX-2) and their mixture for cytokine assays. The structures of L1 and L2 were optimized using density functional theory with the B3LYP/6–311++G(d,p) method. The optimized structures were then docked into the COX-2 active site, revealing slightly lower binding affinities (ΔG = −7.57 and −7.13 kcal/mol, respectively) compared with naproxen (−8.95 kcal/mol). The interactions of the ligands with Ser530 and Arg120 in the arachidonate-binding site predict a potential COX-2 inhibition through π-donor hydrogen interactions, along with several hydrophobic and π–π interactions. In the in vitro assays, both lignans significantly upregulated the anti-inflammatory cytokines interleukin (IL)-6, IL-4, and IL-13, which are involved in host protection against nematodes. By contrast, the chemokine CXCL8 was downregulated, indicating a reduction in inflammatory signaling. Moreover, the combination of L1 and L2 with lipopolysaccharide showed a synergistic effect, increasing the relative expression of IL-13 (212.8-fold), highlighting their immunomodulatory activity. These findings from in silico and in vitro assays suggest that the lignans could have potential anti-inflammatory effects, but direct evidence of COX-2 enzymatic inhibition is still lacking. Further in vivo studies are warranted to validate their therapeutic potential. Further in vivo studies are warranted to validate their therapeutic potential.